Studi Perbandingan Minat Belajar Dalam Permainan Bolavoli Antara Siswa SMPN 1 Dengan Siswa SMPN 3 Sungguminasa Kabupaten Gowa - Ramli Ramli; Hikmad Hakim; Musdalifah Ramli (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2020)
ABSTRACTThis research is a type of descriptive research. This study aims to determine; Comparison of interest in learning in volleyball games between Sungguminasa SMPN I students of Gowa Regency and Sungguminasa SMPN I students.                The population is all students of SMPN I Sungguminasa, Gowa Regency and students of SMPN 3 Sungguminasa, Gowa Regency. The sample used was grade VIII students. A Sunggiminasa SMPN I as many as 30 people and eighth grade students. A SMPN 3 Sunggiminasa Gowa Regency as many as 30 people. The technique of determining the sample is to use saturated samples. The data analysis technique used is descriptive frequency analysis. The results showed that: 1) Interest in learning in volleyball games in students of SMPN I Sungguminasa in Gowa Regency was 124.17 in average value 2) Interest in learning in volleyball games in students in SMPN 3 in Sungguminasa in Gowa Regency was 113.93 in average. In this case, the students of Sungguminasa I Public Middle School have a higher interest in learning volleyball compared to the students of Sungguminasa I Public Middle School ABSTRAKPenelitian ini adalah jenis penelitian deskriptif. Penelitian ini bertujuan untuk mengetahui; Perbandingan minat belajar dalam permainan bolavoli antara siswa SMPN I Sungguminasa Kabupaten Gowa dengan siswa SMPN I Sungguminasa Kabupaten Gowa. Populasinya adalah seluruh  dan siswa/siswi SMPN I Sungguminasa Kabupaten Gowa dan siswa SMPN 3 Sungguminasa Kabupaten Gowa. Sampel yang digunakan adalah siswa/siswi kelas VIII. A  SMPN I Sunggiminasa Kabupaten Gowa sebanyak 30 orang dan siswa/siswi kelas VIII. A  SMPN 3 Sunggiminasa Kabupaten Gowa sebanyak 30 orang. Teknik penentuan sampel adalah dengan menggunakan sampel jenuh. Teknik analisis data yang digunakan adalah analisis deskriptif frekuensi. Hasil penelitian menunjukkan bahwa: 1) Minat belajar dalam permainan bolavoli pada siswa SMPN I Sungguminasa Kabupaten Gowa sebesar 124,17 nilai rata-ratanya 2) Minat belajar dalam permainan bolavoli pada siswa SMPN 3 Sungguminasa Kabupaten Gowa sebesar 113,93 nilai rata-ratanya. Dalam hal ini siswa SMP Negeri I Sungguminasa Kabupaten Gowa memiliki minat belajar dalam permainan bolavoli yang lebih tinggi dibandingkan dengan  siswa SMP Negeri I Sungguminasa Kabupaten Gowa.